Monetary policy surprises, positions of traders, and changes in commodity futures prices - Nikolay Gospodinov; Ibrahim Jamali (Federal Reserve Bank of Atlanta, 2013)
Using futures data for the period 1990 - 2008, this paper finds evidence that expansionary monetary policy surprises tend to increase crude and heating oil prices, and contractionary monetary policy shocks increase gold and platinum prices. Our analysis uncovers substantial heterogeneity in the magnitude of this response to positive and negative surprises across different commodities and commodity groups. The results also suggest that the positions of futures traders for the metals and energy commodities strongly respond to monetary policy shocks. The adjustment of the net long positions of hedgers and speculators appears to be a channel through which the monetary policy shocks are propagated to commodity price changes.
Keywords: G13; G14; G17; 330; commodity prices; monetary policy shocks; futures data; convenience yields; positions of traders; speculators; hedgers